A scheme of initialization at every latitude - FINIZIO, C. (MAUSAM, 1974)
A new scheme of initialization is suggested which can be utilized for regions which extend from middle to low latitudes. In this scheme the two fields of wind and geopotential are analysed independently and teen forced to be balanced by means of a balance equation, in which each of the two fields enters with a weight, that is a continuous function of the latitude, chosen in dependence of the reliability and significance of the two observed fields. The results referring to a SW monsoon situation are finally examined.